Eurig Scandrett (ed) (2020) Public Sociology as Educational Practice: Challenges, Dialogues and Counter-Publics (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
Public Sociology as Educational Practice frames, critically engages with and seeksto further the theory and practice of public sociology as popularised by publicsociologist, Michael Burawoy. Public sociology is about taking sociology outsidethe university, and using it to support ‘publics’ or communities to generateknowledge about society and how it can be changed. To readers of a journal aboutcommunity education this aim will likely sound familiar; the explicit and implicitlinks between arguments for public sociology and the dialogical pedagogy of PauloFreire are clear throughout the book.